The Effect of Nursing Students' Therapeutic Communication Skills on Their Perceptions of Professional Readiness - Merve Bat Tonkuş; Arzu Dikici; Dilara Ekinci (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: The study aimed to examine the effect of nursing students' therapeutic communication skill levels on their perception of professional readiness. Method: The descriptive type research was conducted at a foundation university in Istanbul in the 2022-2023 academic year. It was conducted with 224 nursing students studying in the 4th and 4th grades. "Personal Information Form", "Therapeutic Communication Skills Scale for Nursing Students" and "Professional Readiness Perception Scale in Nursing" were used to collect data. Descriptive statistics, independent samples t-test and one-way ANOVA, and Tukey test for posthoc analyzes were used to analyze the data. Results: A weak positive relationship was found between students' therapeutic communication skill levels and their professional readiness perception levels. It was determined that there were statistically significant differences between the variables of students taking courses on communication skills before, difficulty in communicating with patients, therapeutic communication skill scores and professional readiness perception scores (p <0.05). Conclusion: In the study, it was concluded that the therapeutic communication skill levels and professional readiness perceptions of students who voluntarily chose the nursing profession and thought that their communication skills were good were high.